P69 Pharmacokinetics of a continuous infusion of piperacillin/tazobactam to children using an elastomeric pump (POPPET Study): pilot data from double lumen central lines. Issue 6 (17th May 2019) - Moss, J; Price, V; Paulus, S; Ramos-Martin, V; Melaine, A; Evans, E; Newland, P; Hope, W; Hawcutt, D; Pizer, B
Abstract : Background: Piperacillin/Tazobactam is the first-line antibiotic for the treatment of febrile neutropenia in the UK. There is increasing interest in administration by continuous infusion in adult studies, but paediatric data is lacking. A continuous infusion, if given via an elastomeric pump could also facilitate earlier discharge from hospital. Methods: Children with an oncology/haematology diagnosis admitted to Alder Hey Children's Hospital with febrile neutropenia, normally treated with Piperacillin/Tazobactam via elastomeric device were considered eligible for the study. Patients received 24–36 hours of intermittent dosing before continuous dosing commenced via elastomeric pump. We analysed the data from 5 patients with double lumen central lines as a pilot phase to determine if expanded recruitment to include patients with single lumen lines was possible. Results: Five patients were recruited, four of which had the continuous infusion. The mean Cmax following intermittent dosing of piperacillin and tazobactam from the lumen used for drug administration were 189.7 mg/L, 95% CI [71.7 - 307.9] and 18.5 mg/L, 95% CI [10.7, 26.3] respectively. The mean Cmax following intermittent dosing for the 'empty' lumen were 160.5 mg/L, 95% CI [121.6 - 199.4] for piperacillin and 13.7 mg/L, 95% CI [11.2 - 16.3] for tazobactam. The largest difference seen was on patient 002 with a concentration of piperacillin almost double that seen in the 'empty' lumen (429 mg/L vs 233 mg/L). Conclusion: The lumen used for drug administration has enough residual drug to influence the results, so expanding recruitment to include single lumen lines is not going to be undertaken. The study has been amended to recognise this, and recruitment will continue with double lumen central lines only. Disclosure(s): Nothing to disclose